Development of Company Establishment Arrangements Limited in Indonesia - Joharsah, Joharsah (Cattleya Darmaya Fortuna, 2024)
In frame fulfil​​ demands public For obtain service which fast, Act No. 40 Year 2007 about PT This arrange, Application Submission​ And giving validation status body law, granting approval change budget base, delivery announcement And reception announcement change budget base and/or notification And reception announcement change data other, which is conducted service information system administration body law​ electronically in side still possible use system m inner manual circumstances certain, deed establishment company Which has confirmed and deed change budget base Which has Approved and/or notified to Minister noted in list company And announced in the Supplement to the State Gazette of the Republic of Indonesia carried out by the Minister. Founding father responsible answer in a way personal to deed law​​ which is conducted on time company Not yet get validation as a body law a p abila company when has get ratification as​ body law No in a way firm accept all agreement Which made by founding father or company in a way firm No take​​ transfer everything right And obligation Which arise consequence from agreement Which made by founding father although agreement That No done on Name company or company.